Structure, Challenges and Opportunities for Development of Entrepreneurial Education in Russian Universities - Margarita Zobnina; Anatoly Korotkov; Aleksandr Rozhkov (Foresight and STI Governance, 2019)
This study explores the creation and development of entrepreneurial education tracks in the formation of a University Entrepreneurial Ecosystem (UEE) in certain Russian universities. In particular, the ways in which these tracks promote new venture launches, the commercialization of technologies, and the development of entrepreneurial mindsets and skillsets will be explored.